Perancangan Dan Pembuatan Sistem Informasi Pendaftaran Siswa Baru di SMK Swasta Jambi Medan - Marthin Yohannes Simanjuntak (Jurnal Multidisiplin Indonesia, 2025)
The new student admission system currently running at JAMBI MEDAN PRIVATE VOCATIONAL SCHOOL still uses a manual system. Prospective students must come directly to the school to find out registration information, carry out the registration process and see the announcement of the selection results. This results in frequent queues at school during the admission schedule. From this problem, the author offers a solution in the form of a new student admissions information system built using a web-based programming language so that it can be accessed by prospective students via the internet network. The system development method used is waterfall. With a web-based admission system, the admission process will be easier and faster. Apart from that, reports can be generated automatically by the system. However, this system cannot send notifications using short messages, so for further research a notification system via short messages or SMS should be developed.